Water Quality Monitoring and Assessment - Voudouris, Kostas; Voutsa, Dimitra (IntechOpen, 2012)
The book attempts to covers the main fields of water quality issues presenting case studies in various countries concerning the physicochemical characteristics of surface and groundwaters and possible pollution sources as well as methods and tools for the evaluation of water quality status. This book is divided into two sections: Statistical Analysis of Water Quality Data;Water Quality Monitoring Studies.